Cardiac metastasis of renal cell carcinoma without inferior vena cava involvement: case report - Melih Topçuoğlu; Yakup Yeşilkaya; Abidin Kılınçer (KARE Publishing, 2013)
We report the case of a 51-year-old man with advanced renal cell carcinoma (RCC), without inferior vena cava (IVC) involvement, who was treated with chemotherapy. Computed tomography of the thorax and abdomen revealed metastatic invasion of the liver, mediastinal lymph nodes, right adrenal gland, and the head of pancreas. Heart involvement via the IVC is a well-known pattern of metastasis during RCC progression. There are very few cases worldwide that have reported RCC with cardiac metastasis without IVC involvement.